Perspectives of implementing software packaged system “Personnel Management System of the National Police of Ukraine” into the activities of the National Police of Ukraine - V. A. Korshenko (Bulletin of Kharkiv National University of Internal Affairs)
It has been stated that the effective solution of the tasks of human resourcing and personnel management is one of the main tasks of any organization, institution or enterprise. The National Police of Ukraine is not an exception, and defective planning can lead to the loss of valuable human resources.